A review of predictive control techniques for matrix converters: part I - Rivera, Marco; Wheeler, Patrick; Olloqui, A.; Khaburi, D.A. (2016)
The predictive strategy is a promising alternative to control matrix converters and due to its simplicity and flexibility to include additional aspects in the control, its implementation can be extended to different topologies and industrial applications. This paper presents an overview of the predictive control principles applied to matrix converters and other derived topologies including cascade systems in different industrial applications, such as renewable energy and multi-drive systems.